Technology in Favor of Disability: Prevalence Study in Ecuador - Arias-Flores, Hugo (2021)
People with disabilities and special needs are very important part of the society, their needs have not been covered over time. Globalization and technological development helped identify the importance of various groups with disabilities. In Ecuador, this identification allows this social group to be visible and particularly people with visual disabilities, who represent approximately 11% of the population with disabilities. The objective of this research is to identify Ecuador’s cities that maintain a higher prevalence of people with disabilities. To comply with the study, a descriptive analysis was conducted from public information about people registered by the authorized government control body. Obtaining this information makes it possible to establish a baseline of attention with real data, which allows getting a greater focus on the development of this social group and the attention they should receive